Original Articles: Non–Small Cell Lung Cancer - A Phase I Study of Light Dose for Photodynamic Therapy Using 2-[1-Hexyloxyethyl]-2 Devinyl Pyropheophorbide-a for the Treatment of Non–Small Cell Carcinoma In Situ or Non–Small Cell Microinvasive Bronchogenic Carcinoma: A Dose Ranging Study. Issue 2 (February 2016) - Dhillon, Samjot Singh; Demmy, Todd L.; Yendamuri, Sai; Loewen, Gregory; Nwogu, Chukwumere; Cooper, Michele; Henderson, Barbara W.
ABSTRACT: : Introduction: : We report a phase I trial of photodynamic therapy (PDT) of carcinoma in situ (CIS) and microinvasive cancer (MIC) of the central airways with the photosensitizer (PS) 2‐[1‐hexyloxyethyl]‐2‐devinyl pyropheophorbide‐a (HPPH). HPPH has the advantage of minimal general phototoxicity over the commonly used photosensitizer porfimer sodium (Photofrin; Pinnacle Biologics, Chicago, IL). Methods: : The objectives of this study were (1) to determine the maximally tolerated light dose at a fixed photosensitizer dose and (2) to gain initial insight into the effectiveness of this treatment approach. Seventeen patients with 21 CIS/MIC lesions were treated with HPPH with light dose escalation starting from 75 J/cm 2 and increasing to 85, 95, 125, and 150 J/cm, 2 respectively. Follow‐up bronchoscopy for response assessment was performed at 1 and 6 months, respectively. Results: : The rate of pathological complete response (CR) was 82.4% (14 of 17 evaluable lesions; 14 patients) at 1 month and 72.7% (8/11 evaluable lesions; 8 patients) at 6 months. Only four patients developed mild skin erythema. One of the three patients in the 150 J/cm 2 light dose group experienced a serious adverse event. This patient had respiratory distress caused by mucus plugging, which precipitated cardiac ischemia. Two additional patients treated subsequently at this light dose had no adverse events. The sixth patient in this dose group was not recruited and the study was terminated because of delays in HPPH supply. However, given the observed serious adverse event, it is recommended that the light dose does not exceed 125 J/cm 2 . Conclusions: : PDT with HPPH can be safely used for the treatment of CIS/MIC of the airways, with potential effectiveness comparable to that reported for porfimer sodium in earlier studies.